3D printed white radish/potato gel with microcapsules: Color/flavor change induced by microwave-infrared heating. (August 2022) - Tang, Tiantian; Zhang, Min; Mujumdar, Arun S.; Teng, Xiuxiu
Graphical abstract: Highlights: Stable natural red gromwell pigment and rose essence microcapsules were prepared. Microcapsules changed the color and flavor of printing paste after microwave-infrared (MIR) heating. The color of the printed sample changed in dependence of microcapsule concentration and heating time. Attractive composite printing was realized by using materials with different amounts of microcapsules. Abstract: The feasibility of using microwave-infrared heating (MIR) to stimulate color/flavor changes of 3D-printed white radish and potato gels containing lipid-soluble natural pigment and essence microcapsules was investigated. Natural red gromwell pigment and rose essence were microencapsulated using gum Arabic/maltodextrin/β-cyclodextrin as the wall materials and spray drying as the drying method. The microcapsules were incorporated into white radish and potato powder at different mass ratios (0, 0.3, 0.7, 1, and 2%, w/w) and the mixture were used as 3D printing ink. The storage modulus and loss modulus of printing paste were decreased with the increasing microcapsule addition; however, the viscosity was not significantly affected. The texture properties (hardness, springness, chewiness, and gumminess) of printed samples after MIR were increased significantly. The color and flavor of the samples changed in a microcapsule concentration- and heating time-dependent manner. With the prolongation of heating time, the brightness value ( L *) of the printed sample added with microcapsules was decreased, while the redness ( a *) and yellowness value ( b *) were significantly increased. The results of electronic nose showed that the flavor of 2% (w/w) microcapsule samples was significantly different before and after heating, and the signals of sensors S1, S4, S5, S9, S11, S14, S16, S17 increased significantly after heating. This research has provided insights for the development of novel 3D printed foods with bright colors and unique flavors.